2010
DOI: 10.1002/ccd.22606
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of everolimus‐eluting and paclitaxel‐eluting stents on target lesions with jailed side branches: 2‐year results from the SPIRIT III randomized trial

Abstract: In this post-hoc analysis of the SPIRIT III RCT, patients undergoing stenting of target lesions with jailed side branches with the thin strut and polymer XIENCE V EES compared to the thicker strut TAXUS PES had lower rates of MACE through 2 years due to fewer MIs and TLRs. © 2010 Wiley-Liss, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 19 publications
0
7
1
Order By: Relevance
“…The jailing by stent overlapping zone was another determinant factor, which may lead to having more metal obstacle in the diseased SB ostium. Although the use of PES has been reported as a risk factor to increase the SB occlusion and periprocedural MI, 5,22,23,29 it was not found in the present study. Since these previous studies were comparison between first‐ and second‐generation DES, it suggests that no difference was found in the comparison between first generation DESs (SES and PES), which have similar thicker struts in the present study.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…The jailing by stent overlapping zone was another determinant factor, which may lead to having more metal obstacle in the diseased SB ostium. Although the use of PES has been reported as a risk factor to increase the SB occlusion and periprocedural MI, 5,22,23,29 it was not found in the present study. Since these previous studies were comparison between first‐ and second‐generation DES, it suggests that no difference was found in the comparison between first generation DESs (SES and PES), which have similar thicker struts in the present study.…”
Section: Discussioncontrasting
confidence: 69%
“…Variables included patient background features (female sex, diabetes mellitus, hypertension, hyperlipidemia, prior MI, and hemodialysis), clinical features (acute coronary syndrome and low ejection fraction), lesion parameters (ACC/AHA lesion type B2, type C, calcified lesion, eccentric lesion, and Medina bifurcation classification), procedural characteristics (intravascular ultrasound, Rotablator, predilatation, stent diameter, stent length, maximum inflation pressure, stent to artery ratio in MV, jailing by stent overlap zone and multiple overlapping stents), QCA parameters (preprocedural MLD, %DS, lesion length, and RVD of the MV), stent type (use of PES), SB origin (LAD, LCX, or RCA), SB angle (<45°), and SB TIMI flow grade before intervention. All variables that showed P < 0.1 on univariate analysis, as well as those previously reported to influence SB occlusion such as use of PES, 5,22,23 were entered into a stepwise multiple logistic regression analysis.…”
mentioning
confidence: 99%
“…This approach should provide useful information to assess whether differences of DES design (previously well described in bench testing) may translate in different procedural outcomes. Although, some recent observations from substudies of larger trials not focused on bifurcated lesions have suggested that the angiographic outcome of small SBs may be influenced by the stent platform favoring last-generation DES designs compared with the first-generation paclitaxel-eluting stent (15,16), no published study has systematically and prospectively assessed the SB procedural and angiographic outcome on unselected bifurcated lesions (in which jailed wire protection, SB rewiring, kissing balloon dilation, and SB stenting were eventually performed). Theoretically, as the stent platform of EES is characterized by side cells, which may be deformed by SB ballooning up to larger diameters, it should both facilitate the performance of provisional stenting and provide better angiographic results in the SB than if an SES were used.…”
Section: Discussionmentioning
confidence: 97%
“…We suppose the thinner stent struts, more open cells, and improved polymers of EES compared to PES might be important reasons for fewer adverse events. The SPIRIT trials demonstrated that the superior stent design of EES was associated with less side‐branch occlusion and less tissue injury, which were related to late adverse events …”
Section: Discussionmentioning
confidence: 99%